Remittances, expenditure patterns, and gender: Parametric and semiparametric evidence from Ecuador - Kristin Göbel (IZA Journal of Migration, 2013)
This study estimates the impact of migrants' remittances on households' spending decisions in Ecuador. Applying both parametric and semiparametric techniques, we find strong evidence that remittances enhance expenditures on education, health, and housing, but decrease expenditures on food. This supports the hypotheses that these inflows result in a stronger human capital accumulation and therefore improve the long-run production possibilities. We do not find strong differences in the impact on expenditure patterns of male and female household heads. The sex of the remitter and the receiver affects the expenditure behavior only slightly.
Keywords: C14; C34; D12; F24; J16; 330; naturalisation; Latvia; non-citizens; migrants